1995
DOI: 10.1074/jbc.270.15.8944
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Truncation of the Neurokinin-2 Receptor Causes Enhanced and Sustained Agonist-induced Signaling

Abstract: The G protein-linked receptor for neurokinin A (NKA) couples to stimulation of phospholipase C and, in some cells, adenylyl cyclase. We have examined the function of the C-terminal cytoplasmic domain in receptor signaling and desensitization. We constructed C-terminal deletion mutants of the human NK-2 receptor (epitope tagged) to remove potential Ser/Thr phosphorylation sites, and expressed them in both mammalian and insect cells. When activated, truncated receptors mediate stronger and more prolonged phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 32 publications
3
67
2
Order By: Relevance
“…This is supported by: 1) the fact that binding curves were all uniphasic for co-expressed receptors with different affinities, 2) a shift in affinity for MCP-1 was observed with the co-expression of the hCCR2 and K311stop mutant, and 3) the efficiency of the N285I mutant in inhibiting WEB2086 binding to hPAFR. Our hypothesis is also supported by the results of other groups, which show not only dimeric receptors but also complexes of much higher molecular weight on SDS-polyacrylamide gel electrophoresis for the hPAFR (20,22) and other members of the GPCRs (12)(13)(14)42). One must also consider that these results could be the result of a greater predisposition toward the formation of heterocomplexes than homocomplexes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is supported by: 1) the fact that binding curves were all uniphasic for co-expressed receptors with different affinities, 2) a shift in affinity for MCP-1 was observed with the co-expression of the hCCR2 and K311stop mutant, and 3) the efficiency of the N285I mutant in inhibiting WEB2086 binding to hPAFR. Our hypothesis is also supported by the results of other groups, which show not only dimeric receptors but also complexes of much higher molecular weight on SDS-polyacrylamide gel electrophoresis for the hPAFR (20,22) and other members of the GPCRs (12)(13)(14)42). One must also consider that these results could be the result of a greater predisposition toward the formation of heterocomplexes than homocomplexes.…”
Section: Discussionsupporting
confidence: 74%
“…The formation of heterocomplexes between different receptor subtypes may be an efficient mechanism to control the cellular response. For example, using immunoprecipitation and immunohistochemical studies, hetero-oligomerization between isoforms of the rat D3 dopaminergic receptor has been shown to occur in vivo (12).Multimer formation has been shown or suggested for several other members of the GPCR family (13)(14)(15)(16)(17)(18)(19)(20), including the human PAF receptor (hPAFR) (21, 22) and ␤2-adrenergic receptor (23), but he role of homo-oligomerization is still ill-defined. However, a study on the ␦ opioid receptor suggested that the transition between the oligomeric and monomeric forms of the receptor could be an important step in the internalization process (24).…”
mentioning
confidence: 99%
“…Internalization-de®cient GPCRs can still activate MAPK properly (Budd et al, 1999;Whistler and von Zastrow, 1999), but receptor signaling kinetics are usually dramatically altered. For example, Cterminal truncation of the GPCR for neurokinin A abrogates its internalization in response to ligand stimulation and causes persistent, as opposed to transient, activation of PLC and MAPK in transfected ®broblasts (Alblas et al, 1995(Alblas et al, , 1996Jalink and Moolenaar, unpublished results). Sustained signaling by the internalization-defective mutant GPCR leads to long-term stimulation of cell proliferation and even phenotypic transformation in a ligand-dependent manner (Alblas et al, 1996).…”
Section: Receptor-mediated Endocytosis and Mapk Activationmentioning
confidence: 99%
“…Most likely, signal attenuation mechanisms such as receptor desensitization and receptor internalization kinetics determine the extent to which GPCRs and other receptors can mediate prolonged MAPK activation and induce S phase entry. For example, a desensitization-defective mutant GPCR mediates sustained MAPK activation and stimulates cell proliferation, whereas the wild-type GPCR mediates only transient signaling and is not mitogenic (Alblas et al, 1995(Alblas et al, , 1996.…”
Section: Lpa and S1p: Intercellular Lipid Mediators Acting On Speci®cmentioning
confidence: 99%
“…NK-B has the highest affinity for NK3 but can also bind and activate NK1 and NK2 (47). NK receptor activation results in stimulation of adenylyl cyclase and cyclic AMP generation, as well as activation of phospholipase C and the accumulation of intracellular calcium (58,59). NK receptor expression was not detected in uninduced or induced G1E-ER-GATA-1 cells using a sensitive RT-PCR-based assay (Fig.…”
Section: Gata-1-mediated Activation Of Neurokinin-b Transcriptionmentioning
confidence: 99%